PENGARUH PENGETAHUAN, KEPATUHAN DAN PENGAWASAN MELALUI MODERASI PENERAPAN SISTEM MANAJEMEN K3 PADA INDUSTRI MANUFAKTUR DI KABUPATEN BEKASI DALAM UPAYA MENEKAN ANGKA KECELAKAAN KERJA - Sutomo .; Kohar Sulistiyadi; Soehatman Ramli; Haryadi B Sukamdani (Universitas Sahid Surakarta, 2019)
The purpose of this research is to know whether there is influence of OHS knowledge, OHS compliance and OHS supervision for mafacture company in Bekasi district to the number of work accident through the implementation of Occupational Safety and Health Management (SMK3) system. The three independent variables in this research are knowledge of OHS (X1), OHS compliance (X2), and OHS supervision (X3) and one dependent variable is Occupational Safety and Health Management System (Y).This research uses Quantitative approach with SEM (Structural Equation Modeling) method, data collecting is done by distributing questionnaires to 295 respondents, data processing using Lisrel program, research subject is manufacturing company in Bekasi district industrial area. The result of analysis is known that Knowledge of OHS, OHS Compliance , and OHS Supervisory simultaneously give a significant influence to the implementation of OHS Management System within the company, Lack of knowledge on OHS resulted in lack of Compliance level and lack of Supervision from Institution having authority according to the provisions of law, the forefront of OHS Management System will affect the high of low accidents in company.